Mediating national identity through international broadcasting: A qualitative study of CGTN's cross-cultural - Tian Shasha (Environment and Social Psychology, 2026)
A key element of China's larger initiatives to strengthen soft power and influence how the world views its national identity is its worldwide media strategy. Amidst growing geopolitical rivalry and general scepticism over China's ascent, global television networks such as CGTN are essential in developing and distributing stories for viewers from many cultural backgrounds. The research that is currently available provides little insight into the real discursive mechanisms that are used to develop and transmit national identity since it frequently depends on quantitative audience surveys or generic media critique. Further interpretative research is still required to identify the precise language, images, and representational techniques used in these global broadcasts. By using a qualitative, interpretative methodology centered on desk-based textual analysis of publicly accessible CGTN English-language content, including as news items, documentaries, and promotional materials, this study fills that gap. The analytical frameworks of Soft Power Theory, Representation Theory, and Critical Discourse Analysis are employed to examine how CGTN constructs and communicates aspects of China’s national identity to international audiences. The study explores narrative framing that emphasizes cooperation, modernization, and peaceful development; language choices and translation practices that support cross-cultural accessibility; visual imagery and symbolism that highlight cultural heritage and technological progress; and relational positioning through which China situates itself within broader global discourses. According to the findings, CGTN uses a complex, multi-layered communication approach that gently reframes Western-dominated narratives while legitimizing China's growing influence in international affairs. These tactics engage with prevailing global narratives in a measured manner, foregrounding China’s image as a responsible and cooperative actor in international affairs. The study advances knowledge of how international broadcasting functions as an instrument of cultural diplomacy and soft power projection in a fast-changing global media landscape by exposing these discursive tendencies.